Auditor independence and professionalism influence audit quality at public accounting firms in Medan - Syahputra, Oky; Herliza Rizki, Irma; Wahyuni, Putri; Parhusip, Arisman (Trigin Publisher, 2024)
The purpose of this study is to determine how much influence the Experience and Ethics of Auditors Against Audit Quality. The research methodology used is quantitative descriptive method, the unit of analysis in this study is Public Accounting Firm Dra. Meilina Pangaribuan MM, Public Accounting Firm Drs Katio & Partners and Public Accountant Firm and Joachim Poltak Lian & Partners as many as 30 auditors. The technique of determining the number of samples used in this study is a saturated sample and amounting to 30 auditors. The research method used is the technique of data collection through the distribution of questionnaires conducted regularly based on research objectives. The results showed Independence variable did not affect Quality Audit while Professionalism of Auditor affected Quality Audit at Public Accounting Firm in Medan. F test results show that Independence and Professionalism of Auditor variables affect Audit Quality at Public Accountant Firm in Medan. The results of the coefficient of determination test show that the Quality Audit variable can be explained by the variables of Experience and Ethics of Auditor, while the remaining Quality Audit variables can be explained by other variables not examined in this study such as competence, objectivity, integrity, etc